Grades 3 and 4 adult-type diffuse gliomas: epidemiology and radiomics in Guanajuato, Mexico. - Ayala-Hernández, Luis E.; Gómez-Gómez, Raúl; Gallegos, Armando; Hernández-Estrada, Raúl A. (Revista Mexicana de Neurociencia)
Objective: The objective of the study is to report epidemiological characteristics and prognostic factors of patients with adult-type gliomas treated in the neurosurgery department of the National Medical Center of Bajío, as well as to evaluate, for the 1 time in Mexican patients, surface regularity (SR). Methods: Epidemiological and clinical features were statistically compared with international references. Survival was estimated using the Kaplan-Meier method. Kaplan-Meier curves were compared with the log-rank test. SR was obtained by segmenting magnetic resonance imaging. Results: Median age of patients with glioblastomas was less than that of patients in the United States (p = 0.021). The administration of radiotherapy (RT) and temozolomide (TMZ) prolonged survival (median gain of 35 months). Median SR was 0.6006 and was close to being statistically lower than the value reported in a large cohort (p = 0.09). Conclusions: Glioblastomas were diagnosed at younger ages and appeared to be more aggressive. The administration of RT and TMZ prolonged substantially survival.